Ecological analysis of dragonfly community at forest area with special purposes Muhammadiyah Mataram University - Putu Eka Gunadi; Harry Irawan Johari; Nurhayati; Sukuryadi (Journal of Biology, Environment, and Edu-Tourism, 2025)
Dragonflies, belonging to the suborders Anisoptera and Zygoptera, are important insect groups in biodiversity studies. Their life cycles are highly sensitive to environmental quality and are often used as indicators of habitat conditions. Dragonflies maintain ecosystem balance through predation on small organisms, with a high species diversity of 5,000–6,000 species worldwide. This study aimed to identify dragonfly species in the forest area of Muhammadiyah Mataram University and to gather baseline information on their diversity. Data were collected in June 2025 via purposive sampling with a time-search technique across six observation plots, and subsequently analyzed using ecological indices. The study recorded 17 dragonfly species from six families, totaling 110 individuals, spanning the suborders Anisoptera and Zygoptera. The dominant species included Euphaea lara, Pseudagrion pilidorsum, and Orthetrum sabina. Ecological index analysis showed a Shannon-Weaver diversity of 2.61, a Margalef species richness of 3.40, an evenness of 0.92, and low dominance, reflecting stable ecosystem conditions. Microhabitat factors such as a temperature of 28.2°C, humidity of 78%, and light intensity of 565 lux also supported the biological activity of dragonflies at the study site.